Propuesta para la remoción de 131I a nivel generadores debido a su concentración en los flujos de la PTAR del Salitre (2020)
Essentially, this study offers a proposal for the removal and management of 131I at the generator level that is based on the diagnosis of the activity of 131I in the Salitre WWTP, by studying the capacity of an adsorbent which was modified in its area Superficial so that it had a greater affinity with the research radionuclide (131I) in the first place, the most appropriate agitation time in the adsorption was evaluated and subsequently determined through different KI concentration solutions the stable adsorption of 127I, which obtained favorable results at high concentrations. When repeating the test using 131I with a considerable high activity and free of control, the results of the adsorption process were not satisfactory allowing to demonstrate that the low mass concentration does not favor the adsorption carried out. Subsequently, a design of decay tanks without adsorption was proposed, a decision made based on the results of the experimentation, with technical specifications capable of complying with the discharge regulations in Colombia and finally the total cost of a construction for the construction system was calculated. proposed decay tanks.